2004
DOI: 10.1128/iai.72.8.4331-4335.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and Utilization of Host Cell Phosphoinositides by Salmonella spp

Abstract: Interactions between microbial pathogens and their hosts can be extremely complex. A good example is the facultative intracellular pathogen Salmonella enterica, which causes typhoid fever and gastroenteritis in humans. In order to subvert host cell functions, Salmonella uses type III secretion systems (TTSSs) to translocate effector proteins directly into the host cell. Salmonella pathogenicity island 1 (SPI1) and SPI2 encode two TTSSs that are required for invasion and intracellular survival, respectively. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…However, the in vivo substrates of SopB remain unclear (18), and it is not known how its phosphatase activity mediates Rho family GTPase activation. Data presented here suggest that SopB activates myosin II locally through a Rho/ROCK/ MLC signaling pathway that leads to correct SCV positioning.…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo substrates of SopB remain unclear (18), and it is not known how its phosphatase activity mediates Rho family GTPase activation. Data presented here suggest that SopB activates myosin II locally through a Rho/ROCK/ MLC signaling pathway that leads to correct SCV positioning.…”
Section: Discussionmentioning
confidence: 99%
“…The Salmonella SigD protein, like its homologue IpgD from Shigella , bears domains conserved within the inositol 4‐phosphatase and 5‐phosphatase families in its C‐terminal region, and is known to act both in vivo and in vitro as a phosphatidylinositol and inositol polyphosphate phosphatase (Norris et al ., 1998; Feng et al ., 2001; Marcus et al ., 2001; Niebuhr et al ., 2002; see also Drecktrah et al ., 2004; Terebiznik et al ., 2002 for reviews). All evidence in literature points towards a key role of its enzymatic activity in virulence: (i) expression of SigD in cell lines causes soluble inositol phosphate fluxes (Feng et al ., 2001); (ii) activation of cellular Akt/PKB, which occurs in Salmonella ‐infected cells, depends on the integrity of the catalytic domain of SigD (Steele‐Mortimer et al ., 2000; Marcus et al ., 2001); and (iii) proper formation and maturation of endocytic vesicles during the invasive process requires hydrolysis of PtdIns 4,5–P 2 and PtdIns 3,5–P 2 respectively, by SigD (Terebiznik et al ., 2002; Hernandez et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that either phagosomal escape or the expression of one or more of the pathogenicity island genes may specifically regulate Akt activation, perhaps through interference with host cell phosphoinositide signaling. Indeed, previous reports have shown that the intracellular pathogen Salmonella produces the effector protein SigD/SopB, which can hydrolyze phosphoinositides such as PIP 3 (35). It is tempting to speculate that F. novicida may express a similar molecule that can regulate host cell phospholipid metabolism.…”
Section: Discussionmentioning
confidence: 99%